The Welfare Implications of the European Trucks Cartel - Christian Beyer; Elke Kottmann; Korbinian von Blanckenburg (Intereconomics, 2020)
This paper presents a pragmatic approach to calculating the total economic loss induced by a cartel, focusing on the European trucks cartel (1997–2011). This comprehensible and transparent approach builds on the theory of monopoly pricing and uses the publicly available data of the infringing companies. Overall, a net welfare loss of up to 15.5 billion euro and an overcharge to the amount of up to 7.6% are estimated. This loss to society cannot be offset by fines or private damage claims and should raise awareness for antitrust policy. The findings presented are relevant for both practitioners and policymakers.
Keywords: 330